2012
DOI: 10.1016/j.cognition.2012.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The labial–coronal effect revisited: Japanese adults say pata, but hear tapa

Abstract: The labial-coronal effect has originally been described as a bias to initiate a word with a labial consonant-vowel-coronal consonant (LC) sequence. This bias has been explained with constraints on the human speech production system, and its perceptual correlates have motivated the suggestion of a perception-production link. However, previous studies exclusively considered languages in which LC sequences are globally more frequent than their counterpart. The current study examined the LC bias in speakers of Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…both /bete/ and /tebe/ shifted to /b'te/). Based on these results (extended to Japanese adults by Tsuji, Gonzalez-Gomez, Medina, Nazzi, & Mazuka, 2012), Sato, Vallee, Schwartz, and Rousset (2007) suggested that the LC bias might be explained by the higher articulatory stability of LC sequences compared with CL ones. It is important to emphasize that both articulatory explanations assume the existence of a language-general (that is, non-language specific) LC bias, predicting similar patterns across languages.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…both /bete/ and /tebe/ shifted to /b'te/). Based on these results (extended to Japanese adults by Tsuji, Gonzalez-Gomez, Medina, Nazzi, & Mazuka, 2012), Sato, Vallee, Schwartz, and Rousset (2007) suggested that the LC bias might be explained by the higher articulatory stability of LC sequences compared with CL ones. It is important to emphasize that both articulatory explanations assume the existence of a language-general (that is, non-language specific) LC bias, predicting similar patterns across languages.…”
Section: Introductionmentioning
confidence: 92%
“…However, Japanese adults did show a perceptual CL bias for these plosive sequences, showing the influence of language exposure on perceptual biases as had been previously suggested (Nazzi et al, 2009;Gonzalez-Gomez & Nazzi, 2012a,b,c). Based on these results, Tsuji et al (2012) concluded that in adulthood there are two different biases, a productive LC bias due to constraints of the articulatory system, and a perceptual CL bias based on distributional frequencies in the lexicon. Moreover, these findings suggest that there might be a default LC bias, defined by articulatory constraints, which will partly (but not entirely) determine the structure of the lexicon across languages, and will lead to both production and perceptual LC biases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations